Faktor-Faktor yang Mempengaruhi Peningkatan Kualitas Pendokumentasian Asuhan Keperawatan - Ahmad, Manarrul; Inayah, Lin; Murtiningsih, Murtiningsih; Mulyati, Mulyati; Oyoh, Oyoh (Journal of Telenursing (JOTING), 2024)
This study aims to determine the factors that influence improving the quality of nursing care documentation. The research method used is a literature review through academics: Google Scholar, Neliti, World Scientific, ProQuest, and PubMed. The results of the study showed that from 15 articles obtained, the factors that influence the improvement of the quality of nursing care documentation are motivation, knowledge, workload, attitude, operational standards, supervision, education, work stress, job satisfaction, availability of operational standards, training, lack of staff, managerial room heads, and performance. In conclusion, the factors influencing the quality of nursing care documentation are motivation, knowledge, workload, attitude, operational standards, supervision, education, work stress, job satisfaction, operational standards, training, lack of staff, managerial room heads, and performance. Keywords: Nursing Care, Documentation Quality, Patient Service